2007
DOI: 10.2113/gsecongeo.102.7.1345
|View full text |Cite
|
Sign up to set email alerts
|

Dolomite Fronts and Associated Zinc-Lead Mineralization, Usa

Abstract: This paper provides previously unpublished drill core and mapping evidence of the spatial relationship between regional dolomitization and Mississippi Valley-type (MVT) mineralization in the midcontinent of the United States. Dolomitization is discussed for several key carbonate units and their contained MVT mineralization. This more complete picture of the relationship between regional dolomitization and mineralization provides constraints on models for MVT mineralization and serves as an exploration guide fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…6 .6 and 6 .7) . Except for dolomitisation, replacement textures are not common in these ores, as explained more recently by Harper and Borrok (2007) . These authors have also described a closely related spatial distribution of epithermal dolomite with ore minerals, implying that the same flow produced both sequentially .…”
Section: Chronology the Timing Of Upper Mississippi Valley Type (Umvt)mentioning
confidence: 86%
“…6 .6 and 6 .7) . Except for dolomitisation, replacement textures are not common in these ores, as explained more recently by Harper and Borrok (2007) . These authors have also described a closely related spatial distribution of epithermal dolomite with ore minerals, implying that the same flow produced both sequentially .…”
Section: Chronology the Timing Of Upper Mississippi Valley Type (Umvt)mentioning
confidence: 86%
“…Several studies have revealed a common temporal sequence of alteration and mineralization for most MVT deposits and their country rocks: host limestone→partially dolomitized limestone→dolostone consisting of void-filling saddle dolomite→sulfide orebody (consisting of sulfides and saddle dolomite) (e.g., Sass-Gustkiewicz et al, 1982;Ohle, 1985;Sangster, 1988;Davies and Smith, 2006;Smith, 2006;Harper and Borrok, 2007). This sequence has led to the conclusion that dolomite and metal sulfides in MVT deposits resulted from the activity of a single fluid system (Davies and Smith, 2006); however, some uncertainties remain.…”
Section: Introductionmentioning
confidence: 99%
“…2) in a general case, adapted here to dolomitization. The predicted forward accumulation of ore appears to be confirmed by the fact that Zn deposits in the U.S. midcontinent (Harper and Borrok, 2007) are largest at the final position of the dolomitization front. Also, ore mineral grains formed in late pulses may replace a little dolomite formed in earlier pulses (as in figs.…”
mentioning
confidence: 70%
“…We have loosely adapted their dynamic model to dolomitization in figure 9, which shows that at any given time most or all of the ore formed previously (both in previous pulses of the same slice and in previous slices) accumulates at the current front. In fact Harper and Borrok (2007) have reported that the largest zinc and lead deposits of the midcontinent of the U.S. do occur at the last position of the dolomitization front, against the undolomitized limestone.…”
Section: Self-cannibalization: Mvt Ores Are "Swept" Downflowmentioning
confidence: 99%